إصدار الصكوك الإسلامية ودورها في التنمية الاقتصادية في أفغانستان: Issuing Sukuk and its Role in Economic Development in Afghanistan - Heravi, Farid Ahmad; Ashurov Sharofiddin (International Journal of Al-Turath In Islamic Wealth and Finance, 2023)
الملخص توسعت الهندسة المالية الإسلامية في العالم، واتجهت الأنظار في دول كثيرة إلى أدوات و صيغ التمويل الإسلامي للوصول إلى النمو الاقتصادي؛ ومن أهمها الصكوك الإسلامية، إذ لقيت الصكوك في هذه الأونة الأخيرة نجاحًا ملحوظاً في كثير من الدول الإسلامية و غير الإسلامية، وعالجت العديد من الأزمات المالية فيها؛ لمساهمتها في تحقيق التنمية الاقتصادية وتوفير السيولة، وسد عجز الموازنة العامة، وتقليل البطالة، وزيادة الناتج المحلي والدخل الفردي، فعلى سبيل المثال ساهم إصدار الصكوك في الإمارات العربية المتحدة بعد تمويل أهم المشاريع البنية التحتية مثل ميناء خليفة عام 2012م في ازدياد الناتج المحلي، حيث وصل إلى 18.3 مليار درهم عام 2017م مقارنة بعام 2007م الذي بلغ 181 مليون درهم. كما أصدرت ماليزيا الصكوك السيادية لتمويل البنية التحتية مثل: المطارات ومحطات القطار (MRT) والطرق الرئيسة، مما أفضى إلى ازدياد فرص العمل وتقليل البطالة والفقر، وازدياد الدخل الفردي؛ إذ ارتفع من 600 دولار عام 2003م إلى 11371 في عام 2022م، كما زادت ميزانيتها العامة إلى 57.37% عام 2011م بعد أن كانت تعاني بسبب الأزمة المالية عام 2008م. أما أفغانستان فهي تعاني من المشاكل الاقتصادية، وهذا يتطلب منها أن تعيد النظر في سياستها الاقتصادية بما يحقق تنويع مصادر التمويل الإسلامي خاصة إصدار الصكوك. وقد استخدم الباحث في هذا المقال المنهج الكيفي التحليلي، حيث جمع البيانات من الكتب والمقالات والمجلات والتقارير الرسمية، ثم قام بتحليلها كيفيًّا، وتوصل إلى أن إصدارات الصكوك في أفغانستان وتمويلها يحقق معدلات نمو اقتصادي عالية ويساهم في التنمية المالية. كما يوصي الباحث دولة أفغانستان أن تهتم بإصدار الصكوك والاستثمار فيها لحل الصعوبات المالية. Abstract: Islamic financial engineering has expanded globally, with many countries turning their attention to Islamic finance tools and formulas to achieve economic growth. Among the most important of these is Islamic Sukuk, which has recently seen remarkable success in many Islamic and non-Islamic countries. Sukuk has addressed numerous financial crises in these countries due to its contribution to economic development, liquidity provision, public budget deficit reduction, unemployment reduction, and increases in GDP and individual income. For instance, the issuance of Sukuk in the United Arab Emirates after funding major infrastructure projects like Khalifa Port in 2012 led to an increase in GDP, reaching 18.3 billion dirhams in 2017 compared to 181 million dirhams in 2007. Malaysia also issued sovereign Sukuk to finance infrastructure such as airports, MRT stations, and main roads, leading to more job opportunities, reduced unemployment and poverty, and increased individual income; it rose from 600 dollars in 2003 to 11371 dollars in 2022, and its general budget increased to 57.37% in 2011 after suffering from the 2008 financial crisis. Afghanistan, however, is experiencing economic problems, requiring a reconsideration of its economic policy to diversify Islamic financing sources, especially Sukuk issuance. In this article, the researcher used a qualitative analytical approach, gathering data from books, articles, journals, and official reports, and then qualitatively analyzing them. The study concludes that Sukuk issuances in Afghanistan and their financing achieve high economic growth rates and contribute to financial development. The researcher also recommends that Afghanistan focus on issuing and investing in Sukuk to solve financial difficulties.